Realizing Economic Religiosity: The Role of Philanthropic Islamic Education for ITNY Students - Iqbal, Muh; Lukis Alam; Cahyo Ibrahim Gumilang (IJISH (International Journal of Islamic Studies and Humanities), 2024)
Growing student numbers present a significant opportunity to develop Islamic philanthropy, but a comprehensive introduction to philanthropy is necessary. Purpose: This research describes how Islamic education introduces philanthropy to students through theoretical explanations and project assignments. This research uses a case study and unstructured interviews to collect data from ITNY students. Additionally, a literature review is required to bolster the gathered data. This research demonstrates that teaching philanthropy in the classroom is not the only approach; it also requires tangible actions, which students can achieve through projects. It is crucial to convey to students that philanthropy encompasses not only financial donations but also the creation of engineering products that benefit society, emphasizing the importance of empathy in addressing social issues amidst technological advancements in today's society. 5.0